THE IMPACT OF EU TAXONOMY ON CORPORATE INVESTMENTS - CATERINA LUCARELLI; CAMILLA MAZZOLI; MICHELA RANCAN; SABRINA SEVERINI (Journal of Financial Management, Markets and Institutions, 2023)
The European Union Taxonomy on Sustainable Finance is the first comprehensive classification designed to identify the extent to which an economic activity is environmentally sustainable. This paper investigates how the EU Taxonomy affected corporate investments for Taxonomy-eligible companies compared to non-eligible ones. We applied a difference-in-difference model using a dataset of 130,918 firms from 27 EU Member States, using 2019 as a threshold. Our findings show that the introduction of the EU Taxonomy per se did not result in an increase in corporate investments among Taxonomy-eligible companies; rather, firms’ size and Taxonomy-eligibility uncertainty played a key role in explaining variation in corporate investments. The implications are twofold: the participatory and communication approach of the European Commission implemented with the EU Taxonomy is effective in nudging corporate investments aimed at sustainability. However, this only happens when the regulation provides an unambiguous sector specification. Thus, it is important that the regulatory interventions clearly define what is sustainable.